Anemia as a risk factor for lower respiratory tract infection in children of 6 months to 5 years of age - Vashishth, Dhruv; Sharma, Girdhari Lal; Masand, Rupesh (Indian Journal of Child Health, 2019)
Objective: To determine whether anemia is a risk factor for acute lower respiratory tract infections (ALRTI) in children aging 6 months–5 years. Materials and Methods: Observational case–control study was performed in 540 children in the age group of 6 months–5 years who attended the outpatient and inpatient unit of the department of pediatrics of a tertiary care hospital of Jaipur, during the period from January 2017 to June 2018. 270 cases hospitalized for LRTI who fulfilled the inclusion criteria and 270 healthy age and sex matched controls without any respiratory problems attending outpatient department of the department of pediatrics. Children with congenital anomalies, protein energy malnutrition, tuberculosis, congenital heart defects, HIV, and malignancies were excluded from the study. After a detailed history and anthropometric measurements, complete blood count, C-reactive protein, peripheral blood film examination, reticulocyte count, chest skiagram, Mantoux test were done. Iron profile and detailed anemic investigations are done if hemoglobin level was below 11 g/dl as per the WHO criteria. The sentence in abstract can be framed like this. The norms considered for ALRTI were also considered as per defined by the WHO criteria. Results: Male preponderance was observed (55.2%) in the study group. Most of the children were <2 years of age (59.6%). On auscultation, crepitations were a major finding (64.8%). Out of 270; 240 (88.9%) patients were diagnosed as pneumonia and rest 30 (11.1%) cases as bronchiolitis. Anemic patients were found to be 3.7 times more susceptible to ALRTI in this study (p=0.01). Iron deficiency anemia (IDA) was found in 63.7% of total anemic cases in the study group. In the study group, the mean serum iron level 26.3±7.9 mcg/dl in the anemic cases and 29.11±8.95 mcg/dl in the nonanemic cases. It was observed that with an increase in the severity of anemia among the cases, a concomitant increase in the severity of pneumonia was also observed (p=0.04). Conclusion: Early detection, preventive measures, and aggressive treatment with proper nutrition and medication of anemia; especially, IDA in all children are helpful for prevention of ALRTI.